A brief clinical report documenting a novel therapeutic technique (MEmory Specificity Training, MEST) for depression: a summary of two pilot randomized controlled trials. Issue 1 (20th January 2021) - Sadat Zia, Mahsa; Afkhami, Elham; Taher Neshat-Doost, Hamid; Tavakoli, Mahgol; Mehrabi Kooshki, Hossein Ali; Jobson, Laura
Abstract: Background: Depression has a profound effect on quality of life (QoL) and is associated with rumination, hopelessness and social difficulties. It is important to explore novel intervention techniques that may reduce depression, and also improve rumination, hope and QoL. Aims: In this brief clinical report, we report the findings of two pilot randomized controlled trials examining the feasibility of a potentially important novel clinical technique (MEmory Specificity Training, MEST) on depression, social problem-solving (Study 1), rumination, hope and QoL (Study 2). Method: In Study 1, Iranian women with depression ( n = 24) completed the Beck Depression Inventory-II and Means-Ends Problem-Solving test at baseline, post-training and 2-month follow-up. In Study 2, female students with moderate depression ( n = 24) completed the Ruminative Response Scale, Adult Hope Scale and Short-Form Health Survey at baseline and post-training. Assessors were blind to group allocation. In both studies participants were randomly assigned to MEST or a non-active control group. Results: In both studies, MEST was found to be feasible and associated with low drop-out rates and high rates of self-reported patient and group facilitator satisfaction. There was preliminary evidence that MEST may bring about clinical benefit in terms of depression, social problem-solving (Study 1), QoL, rumination and hope (Study 2). Conclusions: MEST is a promising technique in the treatment of depression.